PSIKOTERAPI ISLAM UNTUK KORBAN PENYALAHGUNAAN NARKOBA - Jannah, Riadatul (Al-Amien Prenduan University, Sumenep, 2025)
This study is intended to determine the application of Islamic psychotherapy as a form of rehabilitation for victims of drug abuse at the Mutiara Lentera Mataram Mandatory Reporting Institution (IPWL), as well as to find out the supporting and inhibiting factors for the application of Islamic psychotherapy at the Mutiara Lentera Mataram Mandatory Reporting Institution (IPWL).The research method used is qualitative research where data collection techniques through observation, interviews and documentation methods with 5 subjects consisting of 4 victims of drug abuse and 1 addiction counselor. The results of the study found that the application of Islamic psychotherapy at the Mutiara Lentera Mataram Mandatory Reporting Institution (IPWL) included applying congregational prayer, dhikr, proper ablution and learning to read the Qur'an as an effort to restore the cognitive, affective and psychomotor functions of victims of drug abuse. In addition, there are supporting factors for the implementation of Islamic psychotherapy including: family (parents, siblings, friends), the environment (community and IPWL officers) is a motivator that fosters confidence and enthusiasm in victims of drug abuse, while inhibiting factors such as mood when carrying out Islamic psychotherapy activities, lack of professionals in the field of Islamic psychotherapy who will help clients, hampered by client activities outside which sometimes interfere with the schedule of Islamic psychotherapy activities that have been determined.